Sentiment analysis of customer reviews on food ordering portals of Bangladesh using natural language processing - Deb, Priom; Bhuiyan, Asibur Rahman; Ahmed, Farhan; Hossain, Md. Rakib; Mahrin, Habiba (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.